Diffuse bilateral cerebral calcification caused by Vein of Galen aneurysmal malformation in a two-year-old child: A rare presentation - Yenewub Muluken Tesfaye, MD; Daniel Zewdneh Solomon, MD, MHA, SCRAD; Yeabsira Feleke Lakew, MD; Sineshaw Muluken Tesfaye, MD; Mesay Tilahun Alemu, MD (Radiology Case Reports, 2025)
Intracranial calcification in pediatric patients below the age of 6 years is almost always pathologic. There are several causes of intracranial calcification, including congenital intracranial arteriovenous malformations, congenital infections, and neoplasms. Vein of Galen aneurysmal malformation is the most common of the congenital intracranial arteriovenous malformations. An untreated vein of Galen aneurysmal malformation causes chronic venous ischemia, leading to parenchymal dystrophic calcification. Here we report a case of a 2-year-old male child with developmental delay, seizure, hydrocephalus, and bilateral diffuse cerebral dystrophic calcification. In conclusion, in an appropriate clinical setting, although very rare, a vein of Galen aneurysmal malformation should be considered in the differential diagnosis of diffuse intracranial calcification, especially after ruling out TORCH infections.